The paradoxes of humanized childbirth care in a public maternity ward in Brazil Paradoxos da humanização em uma maternidade no Brasil. - Tornquist C.S.* (2003)
The maternity ward of the University Hospital in Florianópolis, Santa Catarina, Brazil, attempts to follow World Health Organization guidelines for humanized childbirth care, including the encouragement of non-surgical delivery, breastfeeding, rooming-in, extended family visitation, and reduction of excessive technological intervention in the delivery process. The study focuses specifically on the choice of delivery procedure and on family presence during labor/childbirth, as well as women's experience with labor and breastfeeding.